Phytochemical, Mineral Compounds and Anti-Oxidation Studies on Pistacia Lentiscus Shoot Extract (Global Journal of Medical Research, 2014)
Shoot extracts of Pistacia lentiscus (P. lentiscus ) were investigated for its medicinal importance, by valorizing of some chemical characterization, mineral composition, and study of the antioxidant activity. The photochemical screening of the plants constituents were assessed by using qualitative tests were conducted for the presence of the following active components: alkaloid, Hydrolysable tannins, tannins, phlobatannins, phenol, flavonoids, glycoside, saponins, volatile oil, hydrolysable tannin, protein, cortisone and Anthracanens (anti-oxidation compound) . All were present. Mineral contents of shoot extract were determined by Atomic Absorption Spectrophotometer. The highest levels of potassium (K) and Iron (Fe) were found in Shoot of P. lentiscus from Libya. These findings suggest that shoots of P. lentiscus are potential sources of Iron, potassium and antimicrobial compounds. Also it has a great medicinal value due to the presence of anti-oxidation compound and cortisone.
Keywords: pistacia lentiscus L; phytochemical screening; cortisone; mineral composition; antioxidant activity tannins; phlobatannins; volatile oil; active com